Development of a phenomenological soot model integrated with a reduced TRF-PAH mechanism for diesel engine application. (1st January 2021) - Li, Song; Li, Yu; Liu, Jinping; Meng, Wen; Wang, Mengyan; Cao, Yongsheng; Cao, Shuting; Yao, Longbo; Zhang, Kunpeng
Highlights: A new TRF-PAH mechanism is developed for diesel fuel combustion. The reduced mechanism contains 69 species and 178 reactions. A soot model is newly developed for diesel engine application. Soot model can be utilized for soot yield and distribution predictions. Abstract: A reduced n-heptane/toluene (TRF)-polycyclic aromatic hydrocarbon (PAH) chemistry mechanism, including 69 species and 178 reactions, was developed to simulate the combustion process of diesel fuel. Widespread confirmations were carried out for the reduced TRF-PAH mechanism and it agrees well with experimental ignition delays in shock tubes and species mole fraction profiles in premixed flames. Additionally, combined with the reduced TRF-PAH mechanism, an improved phenomenological soot model was developed and implemented in the KIVA-3V code to model soot formation in diesel engine combustion. The developed soot model is made up of five primary steps: soot inception via four-ring PAH species (A4 ), soot coagulation, acetylene-related surface growth, oxygen- and hydroxyl radical (OH)-induced soot oxidation, and surface deposition through A4 . Experimental results from an optical spray chamber, an optical diesel engine, and a heavy-duty metal diesel engine were used to assess the predictive power of the proposed soot model. The obtained results show that the numerical simulation results of the proposed soot model agree fairly well with those experimental data.